2019
DOI: 10.30538/psrp-odam2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Minimum degree polynomial of graphs obtained by some graph operators

Abstract: The minimum degree matrix MD(G) of a graph G of order n is an n × n symmetric matrix whose (i, j) th entry is min{d i , d j } whenever i = j, and zero otherwise, where d i and d j are the degrees of the i th and j th vertices of G, respectively. In the present work, we obtain the minimum degree polynomial of the graphs obtained by some graph operators (generalized xyz-point-line transformation graphs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…[5] establishes relations between the maximum energy and minimum energy of the shadow and splitting graphs of a graph. In [6], the characteristic polynomial of the minimum degree matrix of graphs obtained by certain graph operations is discussed, along with bounds for the largest minimum degree eigenvalue and minimum degree energy of graphs. [7] provides the energy of a graph class in terms of another graph class after removing a vertex.…”
Section: Introductionmentioning
confidence: 99%
“…[5] establishes relations between the maximum energy and minimum energy of the shadow and splitting graphs of a graph. In [6], the characteristic polynomial of the minimum degree matrix of graphs obtained by certain graph operations is discussed, along with bounds for the largest minimum degree eigenvalue and minimum degree energy of graphs. [7] provides the energy of a graph class in terms of another graph class after removing a vertex.…”
Section: Introductionmentioning
confidence: 99%
“…Many polynomials have been defined to overcome this issue [7–11]. One of them is the M‐polynomial for the TIs that depend on the degree [12–17]. Another is NM‐polynomials that depend on the sum of adjacent vertex degrees [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Where m ij , i, j ≥ 1, is the number of edges uv of G such that {d G (u)), d G (v)} = {i, j} [11]. Recently, the study of M − polynomial are reported in [9,16,17,18,6,4,3].…”
Section: Introductionmentioning
confidence: 99%